PENGARUH INSENTIF PAJAK UNTUK BIDANG TERTENTU - Ihsan, Muhammad; Lukman Hakim Mustaqim, Aziz; Pahala, Indra; Wahono, Puji (CV. Lafadz Jaya, 2024)
This study analyzes the influence of tax incentives on investment decisions in the upstream oil and gas sector in Indonesia, as well as their implications for social justice and state sovereignty. Using the Systematic Literature Review (SLR) approach, this study identifies and evaluates studies related to tax incentives and profit-sharing contracts. The results show that the gross split contract scheme, which replaces the cost recovery scheme, is expected to increase transparency and efficiency in natural resource management. Although designed to attract investment by reducing risk, challenges such as regulatory uncertainty and environmental issues remain. This study found that tax incentives have a positive and significant influence on investment interest, potentially increasing state revenue. However, there are concerns that the scheme could discourage investment in high-cost projects, risking affecting the national economy and energy security. Policy recommendations include the evaluation and adjustment of tax incentive policies, as well as dialogue between the government, contractors, and the community to reach mutually beneficial agreements.